Screening of Tea Extract and Theaflavins for Inhibitory Effects on the Biological Activity and Production of Staphylococcal Enterotoxin A. Issue 11 (11th October 2014) - Shimamura, Yuko; Aoki, Natsumi; Sugiyama, Yuka; Nakayama, Tsutomu; Masuda, Shuichi
Abstract This study aimed to develop a novel method with tea extracts and its components, to reduce the risk of foodborne illnesses caused by the bacterial toxin staphylococcal enterotoxin A (SEA). The potential effect of tea extracts, theaflavins, and epitheaflagallin on staphylococcal growth was studied. A broth microdilution method was used to determine the minimum inhibitory concentration of these samples against an SEA‐producing strain, Staphylococcus aureus C‐29. The following assays were performed to evaluate various effects on concentrations of no effect on staphylococcal growth. The interactions of theaflavin‐rich green tea extracts (TGE), theaflavins, and epitheaflagallin to cultured S. aureus C‐29 were determined using Western blot analysis. As a result, all samples suppressed the binding affinity of the anti‐SEA antibody to SEA. Since these samples could react directly with SEA, we examined whether they could bind to SEA. Our results demonstrated that binding of the anti‐SEA antibody to 4 theaflavins‐treated SEA was inhibited in a dose‐dependent manner. On the other hand, the production of SEA was significantly decreased by treatment with TGE and epitheaflagallin. Based on the finding that TGE and epitheaflagallin inhibit the production of SEA, we further examined the relative expression levels of sea toxin‐encoding genes after treatment with TGE and epitheaflagallin with real‐time RT‐PCR. TGE and epitheaflagallin significantly supressed the gene transcription of SEA in S. aureus C‐29. We then tested whether the samples block the biological activity of SEA in murine spleen cells. TGE, theaflavins, and epitheaflagallin became inactivated the biological activity of SEA. These results suggest that edible and safe compounds in tea can be used to inactivate both pathogens and toxins.